A Comparison of Efficacy and Safety of Two Lipid-Based Lubricant Eye Drops for the Management of Evaporative Dry Eye Disease - Jerkins G (Dove Medical Press, 2020)
Gary Jerkins,1 Jack V Greiner,2,3 Louis Tong,4– 6 Jacqueline Tan,7 Joseph Tauber,8 Ali Mearza,9,10 Sruthi Srinivasan11 1Advancing Vision Research, LLC, Nashville, TN, USA; 2Clinical Eye Research of Boston, Boston, MA, USA; 3Department of Ophthalmology, Harvard Medical School, Boston, MA, USA; 4Singapore National Eye Center, National University of Singapore, Singapore; 5Singapore Eye Research Institute, Singapore; 6Duke-National University of Singapore Medical School, Singapore; 7University of New South Wales, Sydney, NSW, Australia; 8Tauber Eye Center, Kansas City, MO, USA; 9Imperial College Healthcare NHS Trust, London, UK; 10Ophthalmic Consultants of London, London, UK; 11Alcon Research, LLC, Johns Creek, GA, USACorrespondence: Gary JerkinsAdvancing Vision Research, LLC, Nashville, TN 37205, USATel +1 615-502-2871Fax +1 615-915-1825Email drjeyeguy@garyjerkins.comPurpose: The aim of this study was to compare the efficacy of two lipid-based lubricant eye drops in patients with lipid-deficient dry eye.Methods: This Phase IV, multicenter, prospective, double-masked study enrolled adults (aged ≥ 18 years) who had a tear film breakup time (TFBUT) of ≤ 15 seconds(s), and unanesthetized Schirmer I test of ≥ 3 mm to ≤ 12 mm in at least one eye, at both screening and baseline visits. Eligible patients (n=231) were randomized (1:1) and received either Systane® Balance (SYSB; n=117) or Refresh® Optive Advanced (RFO-Ad, n=114), four-times a day, for 35 days. The primary endpoint was non-inferiority for change from baseline in TFBUT at Day 35 (non-inferiority was established if the lower limit of the 95% confidence interval (CI) for the difference between the treatment groups was > – 1.0 s); secondary endpoints (test of superiority) were change in TFBUT and global ocular discomfort visual analog scale (VAS) score at Day 35. Other endpoints included the impact of dry eye on everyday life (IDEEL) treatment satisfaction scores (inconvenience and effectiveness) and safety.Results: At Day 35, the mean change from baseline in TFBUT was 0.998 s in the SYSB and 0.868 s in the RFO-Ad groups with a treatment difference: 0.130 s; (95% CI − 0.34, 0.60; P< 0.0001) demonstrating non-inferiority of SYSB to RFO-Ad. The global ocular discomfort VAS scores improved in both groups, with a mean change from baseline of – 9.7 and – 8.8 in SYSB and RFO-Ad groups (treatment difference – 0.8; P=0.62), respectively. No meaningful difference was observed in IDEEL treatment effectiveness and treatment inconvenience scores between SYSB vs RFO-Ad (P> 0.05 for treatment difference). Both treatments were well tolerated.Conclusion: SYSB lubricant eye drops were non-inferior to RFO-Ad for improvement in TFBUT in patients with lipid-deficient dry eye. Both lubricant eye drops improved TFBUT and ocular discomfort scores in patients with lipid-deficient dry eye.Keywords: dry eye, lipid-deficient, evaporative dry eye, lubricant eye drops, non-inferiority